2019
DOI: 10.1111/jch.13622
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and patients with acute coronary syndrome: Putting blood pressure levels into perspective

Abstract: Arterial hypertension is a well‐established cardiovascular risk factor, and blood pressure (BP) control has largely improved the prognosis of hypertensive patients. A number of studies have assessed the role of BP levels in the prognosis of patients with acute coronary syndromes. Pathophysiologic links of hypertension to acute myocardial infarction (MI) include endothelial dysfunction, autonomic nervous system dysregulation, impaired vasoreactivity, and a genetic substrate. A history of hypertension is highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 59 publications
0
20
0
1
Order By: Relevance
“…In the paper by Konstantinou and associates, 1 I congratulate the authors for the excellent description of the underlying pathophysiology and agree with their speculation that a systolic blood pressure of higher than 110 mm Hg and a diastolic blood pressure lower than 70 mm Hg prior to discharge are associated with better long-term prognosis. This is in agreement with the findings of the randomized trial, Systolic Blood Pressure Intervention Trial that was carried out in persons at an increased cardiovascular risk.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…In the paper by Konstantinou and associates, 1 I congratulate the authors for the excellent description of the underlying pathophysiology and agree with their speculation that a systolic blood pressure of higher than 110 mm Hg and a diastolic blood pressure lower than 70 mm Hg prior to discharge are associated with better long-term prognosis. This is in agreement with the findings of the randomized trial, Systolic Blood Pressure Intervention Trial that was carried out in persons at an increased cardiovascular risk.…”
mentioning
confidence: 59%
“…In the paper by Konstantinou and associates, the authors restate the importance of hypertension as a cause of cardiovascular disease and the effect of this condition on the prognosis of patients with acute coronary syndromes. They describe the pathophysiologic links of hypertension to acute myocardial infarction including endothelial dysfunction, autonomic nervous system dysregulation, impaired vasoreactivity, and a genetic substrate.…”
mentioning
confidence: 99%
“…On the contrary, evidence suggests that prompt, long-term BP control is imperative to improve secondary prevention of MI. 24 Thus, further studies are needed to explore this topic specifically in the Mexican population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, using data from more than 10,000 non-ST-elevation ACS patients in two large registries, Lee et al found an independent relationship between lower SBP and in-hospital mortality; hypertension history or use of antihypertensive medication did not affect these associations [14]. Nevertheless, only a few studies have examined whether admission SBP levels per se might affect hard outcomes in AMI patients [18]. Previous studies have been limited to the association between higher admission SBP and better outcome, so that the specific relationship between admission SBP and adverse outcome is not clearly clarified.…”
Section: Plos Onementioning
confidence: 99%